2016
DOI: 10.1186/s12879-016-1710-0
|View full text |Cite
|
Sign up to set email alerts
|

Pertussis in infants: an underestimated disease

Abstract: BackgroundThe clinical diagnosis of pertussis is not easy in early infancy since clinical manifestations can overlap with several different diseases. Many cases are often misclassified and underdiagnosed. We conducted a retrospective study on infants to assess how often physicians suspected pertussis and the actual frequency of Bordetella pertussis infections.MethodsWe analyzed all infants with age ≤90 days hospitalized from March 2011 until September 2013 for acute respiratory symptoms tested with a Real Time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 37 publications
2
26
1
Order By: Relevance
“…We are careful not to over-interpret this finding, but this could reflect a higher tendency to test, and therefore diagnose, children who are not immunised to rule out respiratory pathogens, with a focus on pertussis. 18 Our study found no difference in immunisation status for children who were diagnosed in ED with an infectious disease compared to children who had other diagnoses. Although it is plausible that immunised children would present less often with infectious disease to ED (especially VPDs), given the low rate of VPDs in the community and the descriptive nature of this proof-of-concept linkage study, the power to find such a difference was likely too low.…”
Section: Discussioncontrasting
confidence: 66%
See 1 more Smart Citation
“…We are careful not to over-interpret this finding, but this could reflect a higher tendency to test, and therefore diagnose, children who are not immunised to rule out respiratory pathogens, with a focus on pertussis. 18 Our study found no difference in immunisation status for children who were diagnosed in ED with an infectious disease compared to children who had other diagnoses. Although it is plausible that immunised children would present less often with infectious disease to ED (especially VPDs), given the low rate of VPDs in the community and the descriptive nature of this proof-of-concept linkage study, the power to find such a difference was likely too low.…”
Section: Discussioncontrasting
confidence: 66%
“…We found that one in five children diagnosed with confirmed RSV were not immunised. We are careful not to over‐interpret this finding, but this could reflect a higher tendency to test, and therefore diagnose, children who are not immunised to rule out respiratory pathogens, with a focus on pertussis …”
Section: Discussionmentioning
confidence: 99%
“…A recent retrospective analysis by Vittucci et al 17 analyzed the presence of pertussis among 215 infants observed over a 3-years period and hospitalized for any acute respiratory symptoms. Even without any specific selective clinical criteria for pertussis, the authors found 24.7% of positivity to pertussis.…”
Section: Discussionmentioning
confidence: 99%
“…For older children and also including parents and other household members should performed measurement of IgG-anti-PT. The culture and PCR recommended to be performed in vaccinated children, adolescents and adults with less than two weeks of coughing, PCR and the measurement of IgG-anti-PT in adolescents and adults with coughing of less than three weeks, and only the measurement is laboratory-confirmed: a case that meets the clinical case definition and is laboratory-confirmed [18].…”
Section: Methodsmentioning
confidence: 99%